2011
DOI: 10.1128/jcm.00336-11
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Prediction of Human Immunodeficiency Virus Type 1 Tropism by Use of Plasma and Peripheral Blood Mononuclear Cells in the Routine Clinical Laboratory

Abstract: We developed a sequencing assay for genotypic HIV-1 tropism determination. The assay allows examination of HIV RNA from plasma and HIV DNA from peripheral blood mononuclear cells (PBMC), including PBMC samples from patients with undetectable viral loads. Assessment of 100 pairs of plasma and PBMC samples showed a high concordance of 90%. With the limitations of population-based sequencing, the assay was found to be robust and suitable for the routine clinical laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…We found a high level of concordance between the two compartments (ϳ84%), confirming findings described previously in other studies (2,11,17,18). With the FPR set at 10%, concordance was found mainly for R5-tropic viruses (83%).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We found a high level of concordance between the two compartments (ϳ84%), confirming findings described previously in other studies (2,11,17,18). With the FPR set at 10%, concordance was found mainly for R5-tropic viruses (83%).…”
Section: Discussionsupporting
confidence: 79%
“…Although the use of MVC after DNA tropism testing has potential, this strategy is not yet recommended in current guidelines, because of the lack of large studies on this topic (6). Several studies showed a high level of concordance between HIV-1 genotypic coreceptor tropism predictions based on plasma RNA and pvDNA findings (2,11,(17)(18)(19), but the factors that might be associated with the discrepancies between the two compartments have not yet been clearly determined. Moreover, little is known about the tropism concordance between the two compartments in patients with virological suppression (viremia levels of Ͻ50 copies/ml).…”
mentioning
confidence: 99%
“…Although clinical evaluations have been generally based on plasma-based genotypic assays, cell-based assays are favored for patients whose viral load is suppressed by ART but for whom a drug change is being considered because of adverse effects or regimen simplification [3]. Although both assays were predictive of a virologic response, discrepancies between genotypic tropism predictions using viral RNA and those using proviral DNA have been reported in many studies [16, 1821, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing DNA and RNA tropism assays have reported concordance rates ranging from 78 to 100 % [1223]. In general, X4-tropic sequences are more frequently drawn from proviral DNA than from viral RNA (clinical meanings) [12, 17, 18, 20, 23], but opposite results have been reported in some studies [16, 19, 21]. However, the causes of these discrepancies are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…4. Finally, in clinical genotypic testing of HIV-1 tropism, from proviral or plasma samples, the importance of testing in triplicates remains elusive and is not as clear-cut as the authors maintain (4,6). As testing in triplicates is tedious and costly and does not readily fit into the work flow of a routine clinical laboratory, it is paramount to scientifically justify this.…”
Section: A Further Principal Issue In Genotypic Testing Of Hiv-1 Tro-mentioning
confidence: 99%